Developing a city-wide, community-engaged cancer disparities research agenda - Amy E. Leader; Yawei Song; Evelyn T. González; Thierry Fortune; Nilsa Graciani; Charnita Zeigler-Johnson; Karen Glanz (Cancer Causes & Control, 2025)
Introduction In response to high levels of cancer disparities in Philadelphia, PA, three NCI-designated clinical cancer centers formed Philadelphia Communities Conquering Cancer (PC3) to bring stakeholders together and establish infrastructure for future cancer reducing initiatives. The PC3 coalition aimed to develop a prioritized cancer disparities research agenda in order to align cancer center resources and research interests with the concerns of the community about cancer, and to ensure that initiatives were patient- and community-centered. Methods Agenda development activities culminated in a city-wide cancer disparities conference. The conference, attended by 55 diverse stakeholders, was the venue for small group discussion sessions about cancer concerns related to prevention, early detection, treatment, survivorship, and quality of life. Sessions were guided by a moderator guide and were audiorecorded, transcribed, and analyzed by the PC3 leadership team. Results were reviewed and consensus was achieved with the help of PC3’s Stakeholder Advisory Committee. Results Stakeholders identified four thematic areas as top priorities for cancer disparities research and action in Philadelphia: communication between patients, providers, and caregivers; education that reaches patients and community members with tailored and targeted information; navigation that assists people in finding and accessing the right cancer screening or treatment option for them; and representation that diversifies the workforce in clinics, cancer centers, and research offices. Conclusion A community-informed, prioritized research agenda provides a road map for the three cancer centers to collaborate on future initiatives that are important to patients and stakeholders, to ultimately reduce the burden of cancer for all Philadelphians.